Help pleaseeee! ASAP!

Accepted Solution

Answer:CStep-by-step explanation:First we simplify what we can in the expressions.  3sqrt(3y) can't be so we leave that.  We want to try and get everythig to have sqrt(3y) in it though.sqrt(27y^5) = sqrt((3^3)y^2y^3) = sqrt(3^2y^4*3y) = 3y^2*sqrt(3y)y^2*sqrt(75y) = y^2*sqrt(5^2*3y) = 5y^2*sqrt(3y)So now we have 3sqrt(3y) - 3y^2*sqrt(3y) + 5y^2*sqrt(3y)If we factor out sqrt(3y) we get (3-3y^2+5y^2)sqrt(3y) = (3+2y^2)sqrt(3y) So that's CLet me know if you don't get how I did something though and I'll be happy to explain it.